Dual-energy CT vital iodine tumor burden for response assessment in patients with metastatic GIST undergoing TKI therapy: comparison with standard CT and FDG PET/CT criteria : gastrointestinal imaging - Meyer, Mathias; Hohenberger, Peter; Overhoff, Daniel; Bartsch, Anna; Henzler, Thomas; Haubenreisser, Holger; Ronald, James; Schmidt, Bernhard; Flohr, Thomas; Sedlmair, Martin Ulrich; Ota, Hideki; Messiou, Christina; et al. (American journal of roentgenology, 2022)
BACKGROUND. CT-based criteria for assessing the gastrointestinal stromal tumor (GIST) response to tyrosine kinase inhibitor (TKI) therapy are limited in part because tumor attenuation is influenced by treatment-related changes including hemorrhage and calcification. The iodine concentration may be less impacted by such changes. OBJECTIVE. The purpose of this study was to determine whether the dual-energy CT (DECT) vital iodine tumor burden (TB) allows improved differentiation between treatment responders and nonresponders among patients with metastatic GIST who are undergoing TKI therapy compared with established CT and PET/CT criteria. METHODS. An anthropomorphic phantom with spherical inserts mimicking GIST lesions of varying iodine concentrations and having nonenhancing central necrotic cores underwent DECT to determine a threshold iodine concentration. Forty patients (25 women and 15 men; median age, 57 years) who were treated with TKI for metastatic GIST were retrospectively evaluated. Patients underwent baseline and follow-up DECT and FDG PET/CT. Response assessment was performed using RECIST 1.1, modified Choi (mChoi) criteria, vascular tumor burden (VTB) criteria, DECT vital iodine TB criteria, and European Organization for Research and Treatment of Cancer (EORTC) PET criteria. DECT vital iodine TB criteria used the same percentage changes as RECIST 1.1 response categories. Progression-free survival was compared between responders and nonresponders for each response criterion by use of Cox proportional hazard ratios and Harrell C-indexes (i.e., concordance indexes). - RESULTS. The phantom experiment identified a threshold of 0.5 mg/mL to differentiate vital from nonvital tissue. With use of the DECT vital iodine TB, median progression-free survival was significantly different between responders and nonresponders (623 vs 104 days; p < .001). For nonresponders versus responders, the hazard ratio for disease progression for DECT vital iodine TB was 6.9 versus 7.6 for EORTC PET criteria, 3.3 for VTB criteria, 2.3 for RECIST 1.1, and 2.1 for mChoi criteria. The C-index was 0.74 for EORTC PET criteria, 0.73 for DECT vital iodine TB criteria, 0.67 for VTB criteria, 0.61 for RECIST 1.1, and 0.58 for mChoi criteria. The C-index was significantly greater for DECT vital iodine TB criteria than for RECIST 1.1 (p = .02) and mChoi criteria (p = .002), but it was not different from that for VTB and EORTC PET criteria (p > .05). CONCLUSION. DECT vital iodine TB criteria showed performance comparable to that of EORTC PET criteria and outperformed RECIST 1.1 and mChoi criteria for response assessment of metastatic GIST treated with TKI therapy. - CLINICAL IMPACT. DECT vital iodine TB could help guide early management decisions in patients receiving TKI therapy.